TimeAware: Leveraging Framing Effects to Enhance Personal Productivity - Kim, Young-Ho; Jeon, Jae Ho; Choe, Eun Kyoung; Lee, Bongshin; Kim, Kwonhyun; Seo, Jinwook (Proceedings of the ACM Conference on Human Factors in Computing Systems, 2016)
To help people enhance their personal productivity by providing effective feedback, we designed and developed TimeAware, a self-monitoring system for capturing and reflecting on personal computer usage behaviors. TimeAware employs an ambient widget to promote self-awareness and to lower the feedback access burden, and web-based information dashboard to visualize people’s detailed computer usage. To examine the effect of framing on individual’s productivity, we designed two versions of TimeAware, each with a different framing setting—one emphasizing productive activities (positive framing) and the other emphasizing distracting activities (negative framing), and conducted an eight-week deployment study (N = 24). We found a significant effect of framing on participants’ productivity: only participants in the negative framing condition improved their productivity. The ambient widget seemed to help sustain engagement with data and enhance self-awareness. We discuss how to leverage framing effects to help people enhance their productivity, and how to design successful productivity monitoring tool.